Topics and methods for urban and landscape design from the river to the project - Ingaramo, Roberta; Voghera, Angioletta (Springer, 2016)
This book combines urban planning and architectural tools in an attempt to overcome the limitations of sectoral measures. In this perspective, it offers a forum for the debate of different approaches used by schools of planning and architecture. It explores strategies by drawing from the potential contributions of cognitive models for decisions, the role of utopian thinking and retrofitting actions and their interconnectedness, the role of cultural legacy for urban and landscape design, the design perspectives about public spaces, and the role of architecture design and urban and regional planning for landscape quality. The book also discusses on design as a process of decision-making that operates as an act of empathy that aligns with human and ecological values - emotional, physical and socio-cultural. Each planning and design act has different possible effects able to help making clear strategic and local actions, contributing to community empowerment and to landscape and local governance. Design activity along the river and multiple experiences (design processes, urban fringe design, agri-urban models, river parks, UNESCO sites, River Contracts, greenbelts and ecological networks), through reflection on design roles, helping to understand the design process and its results at different scales
Keywords: Stadtplanung; Fluss; Landschaftsgestaltung; City planning; Landscape design; Urban landscape architecture